Analysis of the Radial Pulse Wave and its Clinical Applications: A Survey - Jinzhong Yang (IEEE, 2021)
The arterial pulse wave is a physiological signal which can reflect the function of the human cardiovascular system. Owing to the measurement being convenient and safe, radial pulse waves have been often used in noninvasive monitoring of human health, which can further reflect the health status of the cardiovascular system, including information of the aorta and peripheral arteries. Moreover, radial pulse waves can assist clinical diagnosis in the prevention and treatment of cardiovascular disease. This paper systematically reviews the progress in analysis of pulse wave analysis, including pulse wave acquisition, waveform processing, pattern classification, parameter estimation, and clinical applications. In terms of waveform acquisition, this paper reviews a variety of methods to obtain radial pulse waves, including tonometry, photoplethysmography, ultrasound manometry, and flexible tactile pressure sensors. In the aspect of waveform processing, this paper summarizes the methods of radial pulse waves preprocessing and feature extraction. With the rapid development of machine learning and deep learning algorithms, radial pulse waves can be used to identify the status of human cardiovascular systems and to estimate parameters related to cardiovascular function. This paper also discusses the applications of radial pulse waves in clinical practice, including cardiovascular function evaluation and pulse diagnosis in traditional Chinese medicine. Some open-source databases and analysis software are also listed. The current development trend, challenges, and future directions of analysis of radial pulse waves are also offered.